Perkembangan Budaya Instan Melalui Aplikasi Kencan Daring - Abisono, Firya Qurratu’ain (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
Globalization and digitalization have brought significant changes to societal culture, introducing a way of life that emphasizes speed and convenience. Technological advancements have accustomed people to an instant culture, where everything can be achieved quickly without lengthy processes. One manifestation of this culture is online dating applications, which offer ease in quickly and conveniently finding a partner. This article aims to analyze how online dating applications influence instant culture and shape the thinking and social behaviors of their users, using a literature review approach. This research examines various literature on instant culture, online dating technology, and the impact of digitalization on interpersonal relationships in the modern era. The findings indicate that online dating applications have transformed how individuals perceive and form relationships, creating patterns of interaction that are shorter and more superficial. Phenomena such as hookup culture, ghosting, and catfishing exemplify the instant behaviors emerging within the context of online dating. These applications not only facilitate the instant search for partners but also shift societal expectations around romantic relationships—from those previously valued for their long-term commitment to casual, non-committal relationships. Furthermore, this research finds that digitalization and online dating technology contribute to changes in social norms, where romantic relationships are now viewed as something that can be chosen and abandoned quickly. The contribution of this research is to provide a new perspective on how instant culture within online dating affects cultural values and social norms in relationships. By understanding these changes, this study aims to serve as a basis for further research on the impact of digitalization on social relationships and offer guidance for online dating application users in navigating instant culture.